2013
DOI: 10.1016/j.rbmo.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation consultation for women with cancer: are we helping patients make high-quality decisions?

Abstract: To investigate the efficacy of the current fertility preservation consultation process in patients' decision-making and socio-demographic and cognitive factors that may affect patients' decision-making, a prospective pilot survey was conducted at university-based IVF centres and included women aged 18-43 years seen for fertility preservation between April 2009 and December 2010. Patients' views on consultation and decision-making about fertility preservation were measured. Among 52 women who completed the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 26 publications
(39 reference statements)
4
83
1
Order By: Relevance
“…Therefore, the benefit of any additional information with regard to knowledge and feeling supported in DM about FP is clear . However, besides additional written information, referral to a fertility expert for counselling about FP is still of utmost importance (Kim et al, 2013). Indeed, the information in the DA could be a good addition to information received by the gynaecologist, as suggested by our finding that women who were recruited through their gynaecologist (and hence had already received some information on FP) still had similar relative increases in knowledge between measurement moments, when compared to women recruited by their oncologist.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, the benefit of any additional information with regard to knowledge and feeling supported in DM about FP is clear . However, besides additional written information, referral to a fertility expert for counselling about FP is still of utmost importance (Kim et al, 2013). Indeed, the information in the DA could be a good addition to information received by the gynaecologist, as suggested by our finding that women who were recruited through their gynaecologist (and hence had already received some information on FP) still had similar relative increases in knowledge between measurement moments, when compared to women recruited by their oncologist.…”
Section: Discussionmentioning
confidence: 86%
“…The percentage of oncologists who indicated that they understood the preservation treatments for gamete, embryo and ovarian tissues were 60, 30, and 5 %, respectively major issue in the treatment of young patients with cancer. Previous reports show that a threat to future fertility is a significant concern for cancer survivors [3,6,8,9]. Despite the heightened awareness of fertility preservation and the increasing number of patients who are referred to fertility preservation specialists, only a small percentage of patients elect to receive treatment [4,8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show that a threat to future fertility is a significant concern for cancer survivors [3,6,8,9]. Despite the heightened awareness of fertility preservation and the increasing number of patients who are referred to fertility preservation specialists, only a small percentage of patients elect to receive treatment [4,8,10]. This suggests that making decisions about fertility preservation is a complex process for many young patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that cryopreservation of embryos and, more recently oocytes [11], are feasible options for young women facing potentially gonadotoxic cancer treatment who wish to have genetically related children in the future, but a paucity of data exists to facilitate patient counseling in terms of outcomes [3,4,9,[12][13][14]. The aim of this study is to compare the ovarian stimulation and IVF outcomes, most notably total dose of gonadotropins used, number of oocytes retrieved, and number of 2pn embryos obtained, for cancer patients who underwent embryo cryopreservation prior to gonadotoxic treatment to those of an age-matched comparison group with tubal infertility who underwent a fresh IVF cycle within the same three-year period as the cancer patient.…”
Section: Introductionmentioning
confidence: 99%